Flavonoid Compounds From The Leaves Of Kalanchoe Tomentosa And Their Cytotoxic Activity Against P-388 Murine Leukemia Cell - Lilis Siti Aisyah; Yenny Febriani Yun; Ade Akbar Abdilla; Tati Herlina; Euis Julaeha; Unang Supratman (Akta Kimia Indonesia, 2016)
Kalanchoe plant, known as “sosor bebek” in Indonesia is a perennial herb and has succulent leaves. The plant is known in folklore and traditional medicine in Indonesia for the treatment of fever, abscesses, bruises, contused wounds, coughs and skin diseases. During the course of our continuing search for novel cytotoxic compounds, the methanolic extract  of Kalanchoe tomentosa plants showed cytotoxic activity against P-388 murine leukemia cells. The methanolic extract of the fresh  leaves of  K. tomentosa was concentrated and extracted successively with n-hexane, ethyl acetate and n-butanol. The ethyl acetate extract exhibited strongest cytotoxic activity againts P-388 murine leukemia cells. By using the cytotoxic activity to follow the separation, the ethyl acetate fraction was separated by combination of column chromatography on silica gel and preparative TLC on silica gel GF254 to afford a kaempferol-3-O-glycosides (1) and kaempferol-3-O-rhamnoside (2). Compound 1 and 2 showed cytotoxic activity against P-388 murine leukemia cells with IC50 > 100μg/mL and IC50 3.32 μg / mL